Regional Projects Selection based on Multi-Criteria Evaluation - SHALDARBEKOV, Kairat; MUKHANOVA, Gulmira; DOSSOVA, Senymgul; NURMUKHAMBETOVA, Zaure; MUSSAEVA, Gulnar; SHALDARBEKOVA, Karligash (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
One of the most important tasks for regional governments is the selection of the most attractive and potentially successful projects for their region. At the regional level, this problem is complicated by the complexity of various factors and their strategic importance. Currently, there are many methods for selecting regional projects to be included in the development program of the territory. However, many methods are only aimed at assessing the financial appeal of a project. The nature of regional projects is very complex and should be evaluated not only from the point of view of their financial success, but also given the specific characteristics of the region. In this study, we have examined a multi-criteria method for selecting of regional projects based on analytical hierarchic process. In particular, we have developed criterion of project selection at the regional level.